Do dense molecular cores with broad emission spectra at |l| ≈ 5.4°, |b| ≈ 0.4° trace the Galactic bar? A multimolecular line study from HOPS. Issue 4 (3rd February 2020) - Akhter, Shaila; Cunningham, Maria R; Harvey-Smith, Lisa; Nawaz, Mohammad Ali; Jones, Paul A; Walsh, Andrew; de Gouveia Dal Pino, Elisabete M; Falceta-Gonçalves, Diego
ABSTRACT: We used NH$\rm _3$ (1, 1) data from the H$\rm _2$ O Southern Galactic Plane Survey (HOPS) between −60° < l < −2.7° and 3.9° < l < 30° and | b | < 0.5° to identify dense molecular regions/clumps of the Milky Way Galaxy that are likely to form high-mass stars. We identified ∼500 such clumps and in this paper we report on 14 of these clumps near the Central Molecular Zone that show broad emission spectral lines (with observed velocity widths between 19.8 and 47.6 km s −1 corresponding to intrinsic velocity widths between 7.1 and 25.2 km s −1 ). We find that these clumps are grouped into three clusters of dense molecular cores centred at l ≈ 5.4°, −5.4°, and −10°. We name them 'Cluster-1', 'Cluster-2' (also known as 'Bania's Clump 1'), and 'Cluster-3'. We find that the same clumps exhibit broad emission spectra for other molecular lines – NH$\rm _3$ (2, 2), (3, 3), and HC3 N(3 − 2). The antisymmetry of Cluster-1 and Cluster-2 in the l − b plane, and the large velocity dispersion of each clump in these two clusters suggest that clusters 1 and 2 may be associated with the Galactic bar potential x−1 orbits. Our assessments show that the clumps of these three clusters host hot gases and their emission-line broadening are associated with shock heating. We find that Cluster-3 is likely to be undergoing high-mass star formation, as suggested by the presence of emission from H$\rm _2$ O maser and radio recombination line (H69α) from HOPS.